Pengaruh Workplace Spirituality dan Transformational Leadership Terhadap Employee Performance dengan Organizational Citizenship Behavior sebagai Variabel Mediasi Studi pada Perwakilan BPKP Provinsi Sumatera Barat - Rahman, Yudi; Syahrul, Laura; Lukito, Hendra (Ekonomis: Journal of Economics and Business, 2024)
Improving employee performance is a continuous effort needed to achieve the organization's goals, vision and mission. This research aims to examine the influence of employee performance, workplace spirituality, transformational leadership, and organizational citizenship behavior as mediating variables. The population in this study were employees of the West Sumatra Province BPKP Representative. The sample collection technique was purposive sampling, namely 95 employees of the West Sumatra Province BPKP Representative. The data analysis technique uses Structural Equation Modeling (SEM). Based on the tests carried out, it shows that workplace spirituality and transformational leadership have a positive and direct influence on employee performance. Meanwhile, organizational citizenship behavior as a mediating variable shows that it has no indirect influence.